Cytokine production in whole-blood cultures following immunization with an influenza vaccine - Tetsuo Nakayama; Takuji Kumagai; Yasuyo Kashiwagi; Hironori Yoshii; Kenta Honjo; Ritsuko Kubota-Koketsu; Yoshinobu Okuno; Shigeru Suga (Taylor & Francis Group, 2018)
A clinical trial of a quadrivalent split influenza vaccine was performed in the 2014/15 season. Sixty-four subjects aged 6 months to 18 years were enrolled in order to investigate the relationship between cellular and humoral immune responses. Subjects were categorized into two groups by measuring neutralizing antibodies: non-primed naïve/primed or seroconverted/non-seroconverted groups. Whole-blood cultures were stimulated with the H1N1 split antigen before immunization and one month after the first and second immunizations for subjects < 13 years and before and one month after the first dose for those ≥ 13 years in order to investigate cytokine production. Significant amounts of IL-2, IL-12, IL-13, MCP-1, MIP-1β, and TNF-α were detected from one month after the first dose in the naïve group. In addition to these cytokines, the production of IL-1β, IL-4, IL-6, IL-8, IL-10, IL-17, G-CSF, and IFN-γ was enhanced one month after the second dose. No significant increase was noted in the primed group, except in the production of IL-10. In seroconverted subjects, the production of IL-2, IL-4, IL-8, IL-10, G-CSF, MCP-1, TNF-α, and IFN-γ increased one month after the first dose, which was earlier than in the naïve group, whereas no significant cytokine response was noted in subjects without seroconversion. Subjects ≥ 13 years were primed and the production of G-CSF, IL-4, and IL-1β increased in subjects with seroconversion. Whole-blood cultures were also stimulated with the H3N2 split antigen and similar cytokine profiles were obtained. Many cytokines and chemokines, including inflammatory cytokines, were produced in seroconverted, but not non-seroconverted subjects.